(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In the ideological universe of the 19th century, the word freedom, maintained some complexity and multiples meanings. The article analyzes the types of freedom manifest in the political speeches of the insurgent - republican Nicolás Bravo during the different moments of his public life. This will allow contextualizar the relation between his ideological principles and his interes personal. In the long process of training of the Mexican nation the transformation of the civil and political values did to evolve the meaning of said term. The freedom was concebida as an expression of political independence in opposition to the authority that was supporting the control, the oppression, the arbitrariness, the slavery and the despotism, also it was thought about her, it associating with the republican regime, which was demanding the direct and permanent participation of every citizen in the public matters. Together with these two should appear more: one who was pleading for a moderate, freedom aristocratic and opposite to the excesses; and other one that was demanding the attachment irrestricto to the law.